2003
DOI: 10.3141/1832-14
|View full text |Cite
|
Sign up to set email alerts
|

Considering Material Heterogeneity in Crack Modeling of Asphaltic Mixtures

Abstract: Cracking in the asphaltic layer of pavement has been shown to be a major source of distress in roadways. Previous studies in asphaltic mixture cracking have typically not considered the material heterogeneity. A numerical method of analysis is presented that is based on the theory of fracture mechanics, in which the binder and the aggregates are treated as distinct materials. The simulations performed are verified and calibrated from simple and conventional laboratory tests. The study investigates crack evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The distance between the Nth sensor and the source is This set of linear equations has the same four unknowns: the coordinates of the source and the time of the AE event. With at least five sensors and the assumption that the P-wave velocity known, this set of equations can be solved and the first guess can be obtained for the numerical optimization for Equation 3.…”
Section: Ae Source Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance between the Nth sensor and the source is This set of linear equations has the same four unknowns: the coordinates of the source and the time of the AE event. With at least five sensors and the assumption that the P-wave velocity known, this set of equations can be solved and the first guess can be obtained for the numerical optimization for Equation 3.…”
Section: Ae Source Locationmentioning
confidence: 99%
“…This method is of particular benefit to the numerical simulation of fracture in asphalt mixtures with phenomenological models, such as the cohesive zone model (3)(4)(5). The formation of microcracks and how they develop the eventual fracture may lead to improved accuracy of the simulation.…”
Section: Introductionmentioning
confidence: 98%
“…The use of nonlinear fracture mechanics to analytically describe these mechanisms can be extremely challenging, since the fracture patterns typically consist of a main crack, crack branches, secondary cracks, and micro-cracks. Recently, more realistic fracture modeling with heterogeneous microstructure in asphalt concrete has been studied using advanced lattice models and DEM (Chang and Meegoda 1997;Guddati et al 2002;Soares et al 2003;Kim and Buttlar 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed literature review can be found in the reference [5]. Unlike other materials, a relatively few number of studies using a CZM have been carried out for asphalt concrete [5,6]. This is mainly due to complicated features such as viscoelasticity and quasi-brittle behavior inherent in asphalt concrete.…”
Section: Introductionmentioning
confidence: 99%